Doses of enzyme complex in a high-energy diet on performance and carcass traits of feedlot steers - Gabriela Letícia Delai Vigne; Mikael Neumann; Leslei Caroline Santos; André Dochwat; Bruno José Venancio; Julio Cezar Heker Junior; Robson Kyoshi Ueno; André Martins de Souza (Revista Brasileira de Zootecnia, 2018)
ABSTRACT The objective of this study was to evaluate the production performance and carcass traits of feedlot steers fed a high-energy diet supplemented with doses of an enzyme complex (0, 2.5, 5.0, and, 7.5 g animal−1 day−1). Thirty-two ½ Angus ½ Nellore crossbred steers at an average age of 12 months and an average initial weight of 422 kg, were kept in a feedlot for 77 days. The roughage-free diet was composed of a mixture of whole corn grain and a protein-mineral-vitamin mix at a constant ratio of 85:15, on a dry matter basis. A completely randomized block design was adopted, consisting of four treatments and four replicates, in which each replicate was represented by a stall with two animals. Each gram of product added to the diet led to a decrease of 0.0818 kg in daily dry matter intake (DMI), whereas fat thickness at the ribs and at the hindquarter increased by 0.3850 and 0.080 mm, respectively. Feed efficiency increased by 0.0054 kg BW kg DMI−1 per gram of enzyme added. Apparent dry matter digestibility had a quadratic response, with maximum digestion manifested at the dose of 4.78 g animal−1 day−1. The gradual inclusion of enzyme complex reduces the DMI but increases feed efficiency and carcass fat cover of feedlot steers.